Improving the Friction Durability of Magnetic Head-Disk Interfaces by Thin Lubricant Films. (26th July 2016) - Miyake, Shojiro; Suzuki, Shota; Miyake, Masatoshi
Abstract : Nanowear and viscoelasticity were evaluated to study the nanotribological properties of lubricant films of Z-tetraol, D-4OH, and A20H, including their retention and replenishment properties. For A20H and thick Z-tetraol-coated disks, the disk surface partially protrudes, and the phase lag (tan ⁡ δ ) increases with friction. This result is consistent with replenishment of the lubricant upon tip sliding. For the D-4OH-coated disk, thetan ⁡ δ value decreases with tip sliding, similar to the case for the unlubricated disk. The durability of the lubricant-coated magnetic disks was then evaluated by load increase and decrease friction tests. The friction force of the unlubricated disk rapidly increases after approximately 30 reciprocating cycles, regardless of the load. The lubrication state can be estimated by mapping the dependence of friction coefficient on the reciprocating cycle number and load. The friction coefficient can be classified into one of four areas. The lowest friction area constitutes fluid lubrication. The second area constitutes the transition to mixed lubrication. The third area constitutes boundary lubrication. The highest friction of the fourth area results from surface fracture. The boundary lubricating area of the A20H lubricant was wide, because of its good retention and replenishment properties.